Severity of Tardive Dyskinesia and Negative Symptoms are Associated with Poor Quality of Life in Schizophrenia Patients - Othman, Zahiruddin; Ghazali, Malihah; Razak, Asrene Abd; Husain, Maruzairi (Japan International Cultural Exchange Foundation, 2013)
Objective: Aim of this study is to determine the association between tardive dyskinesia (TD) and quality of life (QOL). Methods: Seventy-one stable schizophrenia patients with TD attending psychiatric clinic at Hospital Raja Perempuan Zainab H (HRPZ II) or Hospital Universiti Sains Malaysia (HUSM) between January to November 2011 were assessed by a single rater. TD, QOL and psychopathology were assessed using Abnormal Involuntary Movement Scale (AIMS), Quality of Life Scale (QLS) and Positive and Negative Symptom Scale (PANSS) respectively. The main outcome in this study was QLS total score. Descriptive analysis, simple linear regression and multiple linear regressions were appropriately used in data analysis. Results: Majority of subjects were unemployed (73.2%), single (63.4%), Malay (98.6%) male (70.4%), and on typical antipsychotics before onset of TD (95.8%). The mean duration of illness and mean duration on treatment were 22 (SD 9.9) and 21.8 (SD 10.1) respectively. Mild, moderate and severe TD was experienced by 54.9, 32.4 and 12.7 % of subjects in that order. The mean QLS total score was 52.11 (SD 26.7) with the majority of subjects (76.1%) scored lower than mid score indicating low level of QOL. Employment status, marital status, PANSS negative symptoms and severity of TD were negatively associated with QOL. Conclusions: These fíndiugs convey important message to the health care providers to recognize QOL was significantly and negatively associated with severity of TD and negative symptoms. Further, low QOL was also associated with the subjects being single, unemployed or partially employed.